EFFECT OF COMMON CARP (Cyprinus carpio L) PITUITARY GLAND INJECTED WITH DIFFERENT DOSE ON OVULATION ANDSURVIVAL RATE OF INGIR-INGIR (Mistus nigriceps). - Dewi Aprida Yanti; Nuraini '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from October until Desember 2015 in Hatchery and Fish Breeding Laboratory. Departement of Aquaculture, Faculty of Fisheries and Marine Sciences. University of Riau The aims of this research was to know the effect of common carp (Cyprinus carpio L) putuitary gland injected with different dose on ovulation and survival rate of ingir-ingir (Mystus nigriceps) This research used on experimental method with Completely Randomized Design (CRD), one factor four treathment and three replications. The treatments were : PO : control with NaCl 0,9% (0,2 ml), P1 : Injected with 1:3 dose (1 kg of recipient : 3 kg of donor), P2 : Injected with 1:4 dose (1kg of recipient : 4 kg of of donor) and P3 : Injected with 1:5 dose (1 kg of recipient : 5 kg of donor). The results showed that common carp (Cyprinus carpio L) injected gave an effect on ovulation and survival rate of ingir-ingir (Mystus nigriceps). The treatment in P1 : Injected with 1:3 dose (1 kg of recipient : 3 kg of donor) were the best treatment with an average of latent time 6 hours 22 minutes, Ovisomatic index with 12,43%, fertilization rate (FR) 66,97%, hatching rate (HR%) 75,62% and 4 day survival rate of ingir-ingir larvae with 76,91%.   Key  word : Pituitary gland, ovulation, survival rate, Mystus nigriceps